NILAI NILAI ISLAM PADA WAYANG KULIT, MENJADIKAN PERAN PENTING DALAM PERKEMBANGAN SENI ISLAMI DI INDONESIA - Otok Herum Marwoto (Institut Seni Indonesia Yogyakarta, 2014)
One of the many works of art heritage in Indonesia is a shadow puppet performance(Wayang Kulit). Wayang Kulit is a one of branch of art that is popular and favored by someIndonesian, a work of art that is considering masterpiece based onphilosophical valuecontained in its story.Through the characters and the story, wayang has a role in building nation character.Since wayang is one of Indonesian valuable art tradition, if should be maintained and preservedin order to build and empower nation’s identity. The philosophy values in wayang alwaysincourage people to do a good spare not a harmful things, the spirit of commanding tho goodand fortidding unjust or a tern in the shadow puppet is “Memayu Hayuning Bebrayan Agung”,according to their own beliefs and religion.Islam as a religion that full of value and norm has its own rule for its follower. If thrfollower willing to obey the rule then he or she will get happines in the world and here after.Related to this effort, art is fully needed in the knowledge transfoemation process and valuableIslamic Education.Keyword: leather puppet, Art and Islam Salah satu dari banyak karya seni warisan di Indonesia adalah kinerja wayang kulit(Wayang Kulit). Wayang Kulit adalah salah satu cabang seni yang populer dan disukai olehbeberapa Indonesia, sebuah karya seni yang sedang mempertimbangkan nilai onphilosophicalberbasis karya yang terkandung dalam cerita tersebut.Melalui karakter dan cerita, wayang memiliki peran dalam membangun karakterbangsa. Karena wayang merupakan salah satu seni tradisi yang berharga Indonesia, jika harusdijaga dan dilestarikan dalam rangka membangun dan memberdayakan identitas bangsa. Nilainilaifilsafat wayang selalu incourage orang untuk melakukan cadangan yang baik bukan halyang berbahaya, semangat memerintah tho baik dan fortidding tidak adil atau tern di wayangkulit adalah